Mapuche Mobilities in the Southern Andes of Chile: the Case of a Mapuche Community of Curarrehue, Araucanía Region. (Revista LIDER, 2018)
This study analyzes the mobilities of a Mapuche community located in the Trankura valley. The findings report displacements in diverse spatial scales according to socio-political and economic contexts related to the influence of the process of formation and consolidation of the Chilean national State in mapuche territory. Also, they show the main infrastructures that push or stop the mobility of Mapuche people in their daily lives. Finally, it concludes that mobility is a direct experience in our relationship with the world and marks landmark places, whose meanings vary in certain contexts. Therefore, mobility can be conditioned by domination systems that influence our daily experience.